Novel greener approached synthesis of polyacrylic nanoparticles for therapy and care of gestational diabetes - Xianghong Cheng; Yahui Xu; Qian Jia; Ning Guo; Zhenzhen Wang; Yu Wang (Taylor & Francis Group, 2020)
In the present medical diagnostic method for the therapeutic of gestational diabetes mellitus (GDM), it is problematic and difficult to release successful and secure release of drugs to the exact site. Hence, many researchers have been carried out to bring antidiabetic using modern method to release of drugs for their production. This research work focusses on to provide an assemblage to the recent growth in the field of Ramulus mori extract (RME) loaded on polyacrylic gold nanoparticle for antidiabetics with special highlighting on nursing of GDM. Keynote of gold nanoparticle: diabetes mellitus, nursing, insulin, antidiabetic, drugs, and new system for drug delivery. Rat is used to test the drug delivery system. In vivo examination was not prepared seldom including in this research paper. This research investigation could be a new avenue for the development of drug delivery system of GDM.